Voluntary certification of staff. Changes in the legislation of Ukraine regarding regulation of the activities of a consulting engineer (construction) - Galinskyi, О. (Ways to Improve Construction Efficiency, 2020)
Increasing the volume of construction and increasing the complexity of construction sites requires contracting of competent (certified) specialists, whose certification can be passed on both mandatory and voluntary basis. Article 17 of the Law of Ukraine "On Architectural Activity" until recently provided only mandatory certification of "responsible contractors of certain types of work (services) related to the creation of architectural objects" (architects, design engineers, technical supervisors and experts), which may be conducted by the Ministry of Regional Development of Ukraine, or by its decision self-regulatory organizations in the field of architectural activity. However, mandatory professional certification does not cover all types of construction work (services) that require highly qualified contractors. This problem is solved by the recently adopted Law of Ukraine No. 199-IX, which provides for amendments to the Law of Ukraine "On architectural activity", which voluntary certification of specialists in the field of architectural activity equates to mandatory certification, allows the execution of certain types of work (services), related to the creation of architectural objects to specialists who have received the certificate in the field of professional attestation in the bodies for certification of personnel accredited in accordance with the Law of Ukraine "On accreditation of bodies for assessment of and the information on which can be entered in the Register of Certified Persons of the Ministry of Regional Development of Ukraine with subsequent (after 01.12.2020) inclusion in the Unified state electronic system in the field of construction. Certification of consultant engineer is carried out on a voluntary basis, but, given the importance of its role in the implementation of construction projects, including projects funded by foreign investment, to regulate its activity Law of Ukraine No. 199-IX amended the Law Of Ukraine "On Regulation of Urban Planning Activity", in Article 1 of which provides a terminological definition of the profession "Consulting Engineer" and in Article 11 of the Law of Ukraine "On Architectural Activity", according to which, the obligation to carry out Technical consultants may also be assigned to a consulting engineer. In accordance with the final provisions of Law No. 199-IX, the above amendments to the Laws of Ukraine shall enter into force on March 1, 2020.